Prototype Smart Home With Voice Recognition Berbasis Arduino Uno - Muhammad Siddik Hasibuan (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2019)
Smart home or smart home is a system that can facilitate and increase the comfort of the homeowner specifically in terms of controlling electronic equipment in the house so that it can reduce waste in the use of electronic equipment and provide security to the homeowner so that the electrical short circuit is used the owner is wet. This paper discusses the design of systems in smart homes that can activate or activate electronic equipment in this case only to the lights.Keywords : Smart home, Easy VR, Arduino Uno, Voice Recognition